(untitled) (Journal of the College of Basic Education, 2026)
Graduate students at universities face many problems and social challenges that may weaken their sense of academic well-being. A lack of well-being can lead to maladaptive behaviors, discomfort in the academic environment, decreased life satisfaction, and lower achievement levels, negatively impacting their mood and overall university experience. Emotional creativity plays a crucial role in enhancing intrinsic motivation and increasing academic engagement. Conversely, a lack of emotional creativity may cause students to perceive stressors and critical situations as threats, reducing their ability to manage pressure and solve problems. If students are unable to cope with these challenges, they may experience frustration, despair, and difficulty adapting to both their personal circumstances and the rapidly advancing scientific and technological landscape. Based on these concerns, this research aims to answer the following questions: What is the level of academic well-being among graduate students at the university? What is the level of emotional creativity among graduate students at the university? Is there a correlation between academic well-being and emotional creativity among graduate students? The study seeks to: Determine the level of academic well-being among graduate students. Identify the level of emotional creativity among graduate students. The relationship between academic well-being and emotional creativity among graduate students. The difference in the correlation between academic and emotional and innovative luxury among graduates student in: gender (male/female) and field of study (pure sciences/humanities). To achieve these objectives, the researcher followed these steps: Adopted the Academic Well-Being Scale developed by Al-Saadi (2024), based on the theories of Renshaw and Tomenz (2016). The scale consists of( 39 items) distributed across four domains: university value, academic perseverance, academic satisfaction, and academic self-efficacy. Developed and applied an Emotional Creativity Scale based on the theory of Freil (1999), consisting of( 32 items) across four dimensions: emotional readiness, novelty, effectiveness, and originality. After verifying the psychometric properties of both scales (validity, reliability, and discriminatory power), The scales were administered to a sample of (200) graduate students from four colleges in Al-Mustansiriya University, covering both scientific and humanities disciplines, for the 2024-2025 academic year. The collected data was analyzed using appropriate statistical methods, leading to the following findings: A statistically significant difference was found between the sample’s mean scores and the hypothetical mean of the Academic Well-Being Scale, favoring the sample’s mean scores. This indicates that the participants had a moderate level of academic well-being. A statistically significant difference was found between the sample’s mean scores and the hypothetical mean of the Emotional Creativity Scale, again favoring the sample’s mean scores. This suggests that the participants had an above-average level of emotional creativity. A significant positive correlation was observed between academic well-being and emotional creativity among graduate students. No significant difference was found in the correlation between academic well-being and emotional creativity based on gender. However, a difference was found based on the field of study, favoring students in pure sciences. In conclusion, based on these findings, the researcher provided several recommendations and future research suggestions.